Between Fact and Fiction in the Mediterranean: Revisiting the History, Legend and Legacy of Barbarossa - Μήτος, Ιωάννης (Πανεπιστήμιο Πελοποννήσου, 2016)
The purpose of this study is to shed light on the history and legacy of pirate Barbarossa, as key contributing factor to Mediterranean cultural history. The Barbarossa (“red beard” in Italian) brothers (Uruj or Oruc and Hizr or Hayrettin), were historical figures, notorious pirates in the Mediterranean of the late 15th- early 16th centuries. Especially Hizr (or just Barbarossa), who eventually became High Admiral of the Ottoman Navy and helped the expansion of the Ottoman Empire, has acquired legendary proportions, through folk oral tradition (of which the Greek branch is examined here), having become part of an ongoing Turkish imperialist discourse and a commodity product of contemporary Western civilization. More importantly though, as recent studies on piracy have illustrated, Barbarossa has contributed to the main characteristic of the Mediterranean world: the creation of unity through diversity, or, in other words, through a mosaic of civilizations, cultures and identities that were brought into contact by piracy.
Μεταξύ πραγματικότητας και μυθοπλασίας στη Μεσόγειο: Επανεξετάζοντας την ιστορία, τον θρύλο και την παρακαταθήκη του Barbarossa
Keywords: Πειρατεία πλοίων; Μεσόγειος, Περιοχή της; Μεσόγειος, Περιοχή της--Ιστορία; Μεσόγειος, Περιοχή της--Πολιτισμός; Πειρατεία; Πειρατής; Κουρσάρος; Hayrettin Barbarossa; Μεσόγειος